2001
DOI: 10.1002/jcu.1030
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic diagnosis of ascaris‐induced cholecystitis and pancreatitis in a child

Abstract: We describe the sonographic diagnosis of Ascaris-induced acute cholecystitis and pancreatitis in a 2-year-old girl. Abdominal sonography revealed a grossly distended gallbladder with a thick (0.5-cm) wall. The common bile duct was dilated to 0.6 cm without sludge or calculi. The pancreas was hypoechoic, with an enlarged, 3.3-cm pancreatic head. Sonography showed dilatation of the small- and large-bowel loops, with multiple roundworms in duodenal and colonic loops. Sonography has an important role not only in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…5,12,26 The visualisation of ascaris as a soft tissue mass in a dilated intrahepatic bile duct has also been described and needs to be differentiated from sludge ball, non-opaque gallstones and cholangiocarcinoma.10 An 'impacted worm' sign may be seen, consisting of a long tubular, curved, non-opaque structure with echolucent core, and has a poor prognosis.10 It is well known that sonographic visualisation of ascaris worms within the gallbladder and bile duct is difficult because of their transient passage from there,5,6 and sonographic demonstration of a dilated common duct is suggestive of biliary ascaris in patients with known infection. 12 The transient passage of ascaris through the intrahepatic bile ducts was also documented in one of our patients during real-time examination.…”
Section: Discussionmentioning
confidence: 97%
“…5,12,26 The visualisation of ascaris as a soft tissue mass in a dilated intrahepatic bile duct has also been described and needs to be differentiated from sludge ball, non-opaque gallstones and cholangiocarcinoma.10 An 'impacted worm' sign may be seen, consisting of a long tubular, curved, non-opaque structure with echolucent core, and has a poor prognosis.10 It is well known that sonographic visualisation of ascaris worms within the gallbladder and bile duct is difficult because of their transient passage from there,5,6 and sonographic demonstration of a dilated common duct is suggestive of biliary ascaris in patients with known infection. 12 The transient passage of ascaris through the intrahepatic bile ducts was also documented in one of our patients during real-time examination.…”
Section: Discussionmentioning
confidence: 97%
“…US is a sensitive and specific method for detection of worms in the biliary tree, and it can be repeated frequently to monitor response to therapy and worm movement (2,4,7,8). Sensitivity for detection of pancreatic duct involvement, as in this case, is thought to be less (9).…”
Section: Discussionmentioning
confidence: 92%
“…Ampulla is frequently invaded by adult worm as it is located in upper small intestine. Adult worms migrate to common bile duct, intrahepatic duct, gall bladder or less commonly to pancreatic duct leading to biliary colic, cholangitis or pancreatitis 4 . A large study done in India by Khuroo et al showed that hepato-pancreatic ascariasis as an etiological factor for acute pancreatitis was 23% out of which 2.3% were due to worm in the Ultrasonography is a safe and noninvasive tool for the diagnosis of hepatobiliary and pancreatic complication.It also determines the anatomic position of the worms, their motility and number and the status of the intra and extra hepatic biliary system.…”
Section: Discussionmentioning
confidence: 99%